A postmortem study on morphometry of the human stomach in a Bangladeshi population - Begum, Gul Newaz; Nurunnabi, Abu Sadat Mohammad; Shahriah, Sunjida; Rayhan, Khandaker Abu; Perven, Hosna Ara (Journal of Dhaka Medical College, 2013)
Context: A Cross-sectional, descriptive type of study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2005 to June 2006, to see the variation in the size of the stomach with age in Bangladeshi people. Methods: The study was performed on 60 post mortem human stomach collected from unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into four age-groups including group A (2-16 years), group B (17-22 years) and group C (23-65 years). The length and breadth of each stomach were measured by using a measuring tape. Results: The mean length of the stomach were found 12.18±1.77 cm in group A, 17.74±1.95 cm in group B, and 25.31±1.63 cm in group C. The mean breadth of the stomach were found 6.81±0.40 cm, 8.26±0.57 cm and 9.54±0.45 cm in group A, B and C respectively. The differences between age groups were statistically significant (P<0.001). Conclusion: The length and breadth of the human stomach increase with age. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15598 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 16-18